EXPLORING INTERNAL STANDARDS AND MATRIX MATCHING FOR LANTHANIDES DETERMINATION IN TEA BY LA-ICP-MS - Ana Caroline Vedovato Rubin; Vinicius Machado Neves; Ana Barbosa Viana; Taynara Bonfim Riquieri; Dirce Pozebon; Valderi Luiz Dressler (Química Nova)
Lanthanides (Lns) have been increasingly used in different fields, raising some concerns due to potential adverse effects to human life. In this work, it is proposed a laser ablation-inductively coupled plasma mass spectrometry (LA-ICP-MS) method for Lns determination in tea. Cellulose powder, leave powder and filter paper were evaluated as matrix matched standards and 13C, 103Rh, 115In, 197Au and 205Tl as internal standards (IS). Operating conditions of the LA-ICP-MS system, sample preparation procedures, and spiking samples with IS and standards were optimized. Better conditions of IS mixed with powdered standards or samples was achieved when the powder particles size was lower than 50 μm and 2 mL of IS or standard solutions were added to 500 mg of sample. Best results were obtained using Au as IS and filter paper. The method was applied to Lns determination in mint tea, where Ce, La and Nd concentrations were 580 ± 50, 282 ± 15 and 340 ± 60 ng g–1, respectively. The concentrations of the other Lns were below their limit of quantification (LOQ). The Lns concentrations determined by LA-ICP-MS were in good agreement (95% confidence level, t-test) with those found using ultrasonic nebulization-ICP-MS with a precision better than 20%.